The revenant [videorecording (DVD)] - González Iñárritu, Alejandro; DiCaprio, Leonardo; Hardy, Tom, 1977-; Punke, Michael (20th Century Fox Home Entertainment, 2016)
Inspired by true events, an expedition of the uncharted American wilderness, legendary explorer Hugh Glass is brutally attacked by a bear and left for dead by members of his own hunting team. In a quest to survive, Glass endures unimaginable grief as well as the betrayal of his confidant John Fitzgerald. Guided by sheer will and the love of his family, Glass must navigate a vicious winter in a relentless pursuit to live and find redemption.